Clinical indications associated with opioid initiation for pain management in Ontario, Canada: a population-based cohort study. Issue 8 (August 2018) - Pasricha, Sachin V.; Tadrous, Mina; Khuu, Wayne; Juurlink, David N.; Mamdani, Muhammad M.; Paterson, J. Michael; Gomes, Tara
Abstract : Abstract: Concerns over prescription opioids contributing to high levels of opioid use disorder and overdose have led policymakers and clinicians to seek means to reduce inappropriate and high-dose initial prescriptions. To inform such efforts, we sought to describe the clinical indications associated with opioid initiation and the characteristics of the initial prescriptions and patients through a retrospective population-based cohort study. Our cohort included Ontarians initiating prescription opioids for pain management between April 1, 2015, and March 31, 2016. We identified the apparent clinical indication for opioid initiation by linking prescription drug claims to procedural and diagnostic information on health service records on the day of, and 5 days preceding prescription. Outcomes included initial opioid type, prescription duration, and daily dose (in milligram morphine equivalents), stratified either by indication or indication cluster. Among 653, 993 individuals, we successfully classified 575, 512 (88.0%) people initiating opioids into 23 clinical indications in 6 clusters: dental (23.2%); postsurgical (17.4%); musculoskeletal (12.0%); trauma (11.2%); cancer/palliative care (6.5%); and other less frequent indications (17.7%). Individuals with postsurgical pain received the highest daily doses (40.5% with greater than 50 milligram morphine equivalent), and those with musculoskeletal pain received more initial prescriptions with a duration exceeding 7 days (34.2%). Opioids are initiated for a wide range of indications with varying doses and durations; yet, those who initiated opioids for postsurgical and musculoskeletal pain received the greatest doses and durations of therapy, respectively. These findings may help tailor and prioritize efforts to promote more appropriate opioid prescribing. Abstract : Opioid initiation for postsurgical and musculoskeletal pain is associated with the highest dose and duration at initiation, respectively, relative to other indications.